2015
DOI: 10.2139/ssrn.2585442
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Public Innovation Support in Europe. Does Public Support Foster Turnover, Employment and Labour Productivity?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…However, it has been challenging for all member states to measure the impact of EU-funded programs [39]. The authors in [40] demonstrated that a public program funded from the EU is important for innovation among SMEs, that direct support for R&D across the EU countries has some positive impacts on labor productivity for innovative firms [41], that specific EU country policies focused on corporate R&D have had positive spillover effects [42][43][44], and that public funding has benefits for private R&D [45]. The authors in [46] underlined that using EU structural funds enhances the potential of SMEs to obtain a better competitive position in the market.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, it has been challenging for all member states to measure the impact of EU-funded programs [39]. The authors in [40] demonstrated that a public program funded from the EU is important for innovation among SMEs, that direct support for R&D across the EU countries has some positive impacts on labor productivity for innovative firms [41], that specific EU country policies focused on corporate R&D have had positive spillover effects [42][43][44], and that public funding has benefits for private R&D [45]. The authors in [46] underlined that using EU structural funds enhances the potential of SMEs to obtain a better competitive position in the market.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Indeed, one study finds that only 2 % of the surplus of innovation is captured by the original inventor (Nordhaus, 2004). Based on the notion of positive externalities from R&D, inefficient capital markets and because incentives for private R&D investment might be insufficient, all OECD countries currently spend significant amounts of money subsidizing firms and innovation in the form of direct transfers, subsidized loans, tax reductions, exemptions and government backed venture capital (GVC) (Becker, 2015b). Many countries also use laws and legalization as a way to force firms to increase innovation, e.g., by increasing emission standards to force car producers to develop more fuel-efficient cars.…”
Section: Henry Sidgwick -Principles Ofmentioning
confidence: 99%
“…Such analyses have been conducted for many years, with focus on the evaluation of state aid. L. Becker (2015), after the review of the literature for the years 2000-2014, emphasises the ambiguity of the results of many previous studies, drawing attention to the variety of measures of efficiency of state aid for SMEs. They include: labour productivity, job creation, turnover or return on sales.…”
Section: Literature Reviewmentioning
confidence: 99%